Urinary level of 1,N6‐ethenodeoxyadenosine, a marker of oxidative stress, is associated with salt excretion and ω6‐polyunsaturated fatty acid intake in postmenopausal Japanese women - Hanaoka, Tomoyuki; Nair, Jagadeesan; Bartsch, Helmut (International journal of cancer, 2002)
Excretion of 1,N6‐ethenodeoxyadenosine (ϵdA), a marker for lipid peroxidation (LPO)‐derived DNA damage was analyzed in urine of nonsmoking postmenopausal women participating in a dietary intervention...
Im Titel ist "6" bei 1,N6-ethenodeoxyadenosine hochgestellt
Gesehen am 12.01.2021